2022
DOI: 10.1101/2022.08.01.498998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Role for the Fornix in Temporal Sequence Memory

Abstract: Converging evidence from studies of human and nonhuman animals suggests that the hippocampus contributes to sequence learning by using temporal context to bind sequentially occurring items. The fornix is a white matter pathway containing the major input and output pathways of the hippocampus, including projections from medial septum, and to diencephalon, striatum, and prefrontal cortex. If the fornix meaningfully contributes to hippocampal function, then individual differences in fornix microstructure might pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 110 publications
(182 reference statements)
0
6
0
Order By: Relevance
“…Here, we expanded on these findings, linking scene oddity accuracy to more specific features of fornix microstructure. Redundancies in several microstructure measures were exploited to reveal two biologically interpretable components, which were similar to those described in previous studies that used similar PCA methods (Chamberland et al, 2019;Geeraert et al, 2020;Read et al, 2023). PC1 was most influenced negatively by MD, RD and positively by FR and MPF, and was interpreted as positively relating to a 'tissue restriction'…”
Section: Fornix Tissue Restriction Linked To Scene Oddity Accuracymentioning
confidence: 69%
See 4 more Smart Citations
“…Here, we expanded on these findings, linking scene oddity accuracy to more specific features of fornix microstructure. Redundancies in several microstructure measures were exploited to reveal two biologically interpretable components, which were similar to those described in previous studies that used similar PCA methods (Chamberland et al, 2019;Geeraert et al, 2020;Read et al, 2023). PC1 was most influenced negatively by MD, RD and positively by FR and MPF, and was interpreted as positively relating to a 'tissue restriction'…”
Section: Fornix Tissue Restriction Linked To Scene Oddity Accuracymentioning
confidence: 69%
“…Density Index (NDI); and Orientation Dispersion (OD). This larger metric space was then reduced through PCA, a technique that has been shown to be effective in capturing biologically informative features of white matter microstructure (Chamberland et al, 2019;Geeraert et al, 2020;Henriques et al, 2023;Read et al, 2023). The results from the PCA (KMO: 0.66, sphericity: p<0.0001; Figure 3) showed that 94% of the microstructure data variance was accounted for by the first two principal components, PC1 and PC2.…”
Section: Hippocampal Theta Power Modulation Correlates With Scene Odd...mentioning
confidence: 99%
See 3 more Smart Citations